2019
DOI: 10.3390/microorganisms7060156
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence and Decennary Distribution of Clade 2.3.4.4 HPAI H5Nx

Abstract: Reassortment events among influenza viruses occur naturally and may lead to the development of new and different subtypes which often ignite the possibility of an influenza outbreak. Between 2008 and 2010, highly pathogenic avian influenza (HPAI) H5 of the N1 subtype from the A/goose/Guangdong/1/96-like (Gs/GD) lineage generated novel reassortants by introducing other neuraminidase (NA) subtypes reported to cause most outbreaks in poultry. With the extensive divergence of the H5 hemagglutinin (HA) sequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 77 publications
(276 reference statements)
2
63
0
Order By: Relevance
“…Therefore, we infer a high probability of H5N6 transmission from terrestrial birds to domestic poultry at these common habitats. This inference is consistent with pilot studies that suggested an increased risk of viral transmission between these two bird species [40,41]. On the basis of the tMRCA, the divergence of viruses circulating among wild and domestic birds may have occurred 1-3 years earlier compared with those within wild bird populations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, we infer a high probability of H5N6 transmission from terrestrial birds to domestic poultry at these common habitats. This inference is consistent with pilot studies that suggested an increased risk of viral transmission between these two bird species [40,41]. On the basis of the tMRCA, the divergence of viruses circulating among wild and domestic birds may have occurred 1-3 years earlier compared with those within wild bird populations.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our analysis may not represent the gene pool of AIVs in domestic birds in Poyang Lake. Furthermore, H5 clade 2.3.4.4. viruses have diverged into four genetic subgroups together with their worldwide diffusions [ 41, 42 ]. The H5N6 clade 2.3.4.4 viruses isolated in our study fall into two subgroups, indicating that genetic variation among these H5N6 viruses from Poyang Lake does not fully reflect the overall variations of clade 2.3.4.4 viruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, HPAI H5N6 subtype viruses from the same clade caused multiple outbreaks in China, Viet Nam, and Lao People's Democratic Republic and was associated with the first HPAI non-H5N1 virus human infection, in April 2014 in China 9 , 10 . Currently, H5N6 viruses have spread to multiple countries in Europe, the Middle East, and Africa 11 . A total of 24 laboratory-confirmed human cases have been reported in China that include at least 7 deaths 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The process of genome reassortment plays an important role in this. Some subtypes may evolve and acquire a pathogenic phenotype that causes serious disease and is associated with epizootics and pandemics (such as H5Nx and H7Nx) [3,4]. Highly pathogenic avian influenza viruses (HPAIVs) originate from low-pathogenic precursors with the HA subtypes H5 and H7 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Some subtypes may evolve and acquire a pathogenic phenotype that causes serious disease and is associated with epizootics and pandemics (such as H5Nx and H7Nx) [3,4]. Highly pathogenic avian influenza viruses (HPAIVs) originate from low-pathogenic precursors with the HA subtypes H5 and H7 [3,4]. However, the avian influenza virus subtypes H2, H4, H8, and H14 have been shown to support a highly pathogenic phenotype after the genetically engineered introduction of the polybasic cleavage site into the HA [5].…”
Section: Introductionmentioning
confidence: 99%